Uji Toksisitas Ekstrak Metanol Daun Kecubung (Datura metel L) Menggunakan Metode BSLT (Brine Shrimp Lethality Test) - A. Mu’thi Andy Suryadi; Moh Adam Mustapa; Muhammad Taupik; Beby Bestari (Indonesian Journal of Pharmaceutical Education, 2022)
Amethyst plant (Datura metel L.) is often used by people as traditional medicine. This plant contains alkaloids, flavonoids, saponins, tannins, and steroids. Meanwhile, some of these compounds with certain levels can be cytotoxic. Toxicity test using the Brine Shrimp Lethality Test (BSLT) method is an initial screening to test a plant that has cytotoxic potential for the development of anticancer drugs. The purpose of this study was to determine the toxicity of the methanol extract of the leaves of Amethyst (Datura metel L.) to shrimp larvae (Artemia salina Leach) using the BSLT method. The test was carried out using several concentration variations, which are 10, 20, 40, 80, and 160 μg/Ml, and a control solution with 3 replications. Each concentration used 10 larvae, and observations were made for 24 hours on larval mortality. Thus, the findings found that the methanol extract of the amethyst leaf (Datura metel L) was potentially very toxic with an LC50 value of 46.1636 μg/mL.